Conversion Out of Islam and Its Legal Implications Under The Laws of Malaysia - Mohd Nasran Mohammad; Zuliza Mohd Kusrin (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2017)
The freedom to profess and practice religion is one of the basic rights in Malaysia that often catalysis legal issues and discussions. The provision in Article 11 of the Federal Constitution of Malaysia generally guarantees the said right to a person to practice his religion of choice; however, Muslims or practitioners of Islam are not as free as the non-Muslims in the matter of their conversion or reconversion to another religion. This article focuses on the actions or process for a Muslim’s conversion to other religion and the legal ramifications of such actions. This discussion identifies several actions of apostasy, such as issuing a declaration of conversion via a Deed Poll, requesting a Muslim name to be changed to a non-Muslim’s, and renouncing Islam altogether and reverting to a previously held religion (reconversion). There are legal implications for these said actions, such as fines and detention at Aqidah Rehabilitation Centres, which clearly shows that the freedom to practice religion or conversion to other religions as found in Article 11 of the Federal Constitution of Malaysia applies to non-Muslims only. In cases relating to determination of the status of Islam as a religion, the Shariah Court have been given exclusive jurisdiction to hear those cases, as mentioned in the amendment to Article 121(1A) of the Federal Constitution.